2006
DOI: 10.1016/j.jhazmat.2006.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate removal from aqueous solutions using raw and activated red mud and fly ash

Abstract: The effect of acidification and heat treatment of raw red mud (RM) and fly ash (FA) on the sorption of phosphate was studied in parallel experiments. The result shows that a higher efficiency of phosphate removal was acquired by the activated samples than by the raw ones. The sample prepared by using the RM stirred with 0.25 M HCl for 2 h (RM0.25), as well as another sample prepared by heating the RM at 700• C for 2 h (RM700), registered the maximum removal of phosphate (99% removal of phosphate). This occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
144
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(160 citation statements)
references
References 25 publications
12
144
0
4
Order By: Relevance
“…The utilization of low-cost and easily available materials as the filter media has been widely demonstrated by previous studies for their reliability and contribution in the removal of phosphate including fly ash [4], limestone [5], iron oxide tailings [6], blast furnace slag [7], basic oxygen furnace slag and electric arc furnace slag [8].…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of low-cost and easily available materials as the filter media has been widely demonstrated by previous studies for their reliability and contribution in the removal of phosphate including fly ash [4], limestone [5], iron oxide tailings [6], blast furnace slag [7], basic oxygen furnace slag and electric arc furnace slag [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous results have shown that substrate adsorption plays the most important role in P immobilization [4][5][6][7][8]. Therefore, cheap and effective P adsorbents are highly desirable [9][10][11].The most commonly used substrates in CWs are quartz sands [12], activated carbon (AC) [12][13], zeolite [14], ceramic [15], and furnace slag [16][17], and prior research has shown that the removal of P by these substrates mainly occurs though physical adsorption, chemical precipitation, and ion exchange [10][11]. However, P sorption properties of the substrates have not been systematically estimated, which resulted in many defective packing layer designs for CWs [3,11].…”
mentioning
confidence: 99%
“…Previous studies have shown that the adsorption capacity of the phosphorus exists in many lowcost sorbents, such as fly ash [13], bentonite, natural zeolite, alum sludge [14], red mud [15][16][17][18], and other waste materials [19]. Red mud (RM) is a waste residue formed after the caustic digestion of bauxite during the production of alumina.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…The visible light from the high-pressure mercury lamp (125 W) irradiated perpendicularly to the solution and the distance between the lamp and the liquid level was 30 cm. At given irradiation time intervals (5,15,30,45,60, and 90 min), liquid samples were taken from the suspension and settled for 4 h, and then, the phosphorus in the supernatant was measured. …”
Section: Photocatalytic Testmentioning
confidence: 99%